2021
DOI: 10.1002/bse.2867
|View full text |Cite
|
Sign up to set email alerts
|

Industry 4.0, innovation, and sustainable development: A systematic review and a roadmap to sustainable innovation

Abstract: Despite the recent interest in the Industry 4.0 applications for sustainability, little is known on the processes through which digital transformation and Industry 4.0 technologies enable sustainable innovation in manufacturing. The present study addresses this knowledge gap by developing a strategic roadmap that explains how businesses can leverage Industry 4.0 technologies to introduce sustainability into innovative practices. For this purpose, the study conducts a systematic review of extant literature to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
127
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 179 publications
(135 citation statements)
references
References 106 publications
3
127
0
5
Order By: Relevance
“…At the 15th G20 Leaders' Summit in November 2020, Chinese President Xi Jinping stated that China needs to strengthen digital infrastructures, harness roles of the digital economy, address the challenges posed by the digital economy to vulnerable groups, and seek to bridge the digital divide. Ghobakhloo et al (2021) believed that digitization provides opportunities for sustainable development. Usman et al (2021) indicated that information technology, regarded as the core of the digital economy, helps promote economic growth and reduce energy consumption.…”
mentioning
confidence: 99%
“…At the 15th G20 Leaders' Summit in November 2020, Chinese President Xi Jinping stated that China needs to strengthen digital infrastructures, harness roles of the digital economy, address the challenges posed by the digital economy to vulnerable groups, and seek to bridge the digital divide. Ghobakhloo et al (2021) believed that digitization provides opportunities for sustainable development. Usman et al (2021) indicated that information technology, regarded as the core of the digital economy, helps promote economic growth and reduce energy consumption.…”
mentioning
confidence: 99%
“…Digitalization among the food supply chain members are vital to gain social, environmental and economic advantage (Ozkan‐Ozen et al, 2020). Information technologies improve knowledge‐based manufacturing systems, green business performance and sustainable partnerships (Ghobakhloo et al, 2021). As a theoretical background, the adoption of the stakeholder theory can be used to understand these intertwined interactions amidst different tiers of the supply chain in order to value creation, knowledge, and strong networks, as well as integrating these concepts and values among multi‐tiers by management decisions made within the organization.…”
Section: Discussionmentioning
confidence: 99%
“…Adopting Industry 4.0 efforts to supply chain operations as one of the current trends may boost a company's overall sustainability performance [128]. In terms of economic performance, implementing these innovative technologies in the supply chain may save money by boosting productivity and providing a greater return on investment.…”
Section: Conclusion and Future Researchmentioning
confidence: 99%